A comparison of adoption models for new mobile media services between high- and low-motive groups. (1st September 2010) - Lee, Jong Hyuk; Kim, Joon Ho; Hong, Jin Hwan
This study aimed to explore what factors influence mobile media users' adoption of new services and whether the adoption models differ depending on users' motives to use mobile media. The decomposed Theory of Planned Behaviour (TPB) and uses and gratifications theory were used as theoretical frameworks. Methodologically, an online survey was conducted with 400 Korean mobile users and structural equation modelling was employed. As a result, the proposed model explained well users' adoption intention for new mobile services. Especially, high- and low-motive groups showed significant differences in terms of the influence of subjective norms and Perceived Behavioural Control (PBC).